2008
DOI: 10.1371/journal.pbio.0060114
|View full text |Cite
|
Sign up to set email alerts
|

Distinct DNA Exit and Packaging Portals in the Virus Acanthamoeba polyphaga mimivirus

Abstract: Icosahedral double-stranded DNA viruses use a single portal for genome delivery and packaging. The extensive structural similarity revealed by such portals in diverse viruses, as well as their invariable positioning at a unique icosahedral vertex, led to the consensus that a particular, highly conserved vertex-portal architecture is essential for viral DNA translocations. Here we present an exception to this paradigm by demonstrating that genome delivery and packaging in the virus Acanthamoeba polyphaga mimivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
186
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(203 citation statements)
references
References 37 publications
15
186
0
2
Order By: Relevance
“…At 2 h postinfection (PI) of Acanthamoeba polyphaga cells, Mimivirus particles are detected within host phagosomes. A large-scale opening of the viral icosahedral capsid at a unique vertex-centered structure, coined the stargate, results in the formation of a massive channel, which was previously proposed to enable delivery of the internal genome-containing Mimivirus core to the host cytoplasm (10). To appraise this conjecture, electron microscopy studies were conducted on Mimivirus-infected cells at early (2 h) PI time points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 2 h postinfection (PI) of Acanthamoeba polyphaga cells, Mimivirus particles are detected within host phagosomes. A large-scale opening of the viral icosahedral capsid at a unique vertex-centered structure, coined the stargate, results in the formation of a massive channel, which was previously proposed to enable delivery of the internal genome-containing Mimivirus core to the host cytoplasm (10). To appraise this conjecture, electron microscopy studies were conducted on Mimivirus-infected cells at early (2 h) PI time points.…”
Section: Resultsmentioning
confidence: 99%
“…With a genome considerably larger than all currently documented viral genomes, the hurdles inherent for DNA translocations during Mimivirus infection are unparalleled, thus rendering its replication cycle an appealing case study. It was previously shown that a large-scale opening of the Mimivirus capsid at a unique vertex, coined the stargate (10)(11)(12), enables rapid release of the genome-containing internal core into the host cytoplasm (10). Ensuing infection events remain, however, poorly understood.…”
mentioning
confidence: 99%
“…The unique features of Mimivirus revived the debate about the evolution of DNA viruses (Claverie 2006;Claverie et al 2006;Iyer et al 2006) and their position in the Tree of Life (Brüssow 2009;Claverie and Ogata 2009;Moreira and Lopez-Garcia 2009). The complex Mimivirus particle has been the object of detailed proteomic (Renesto et al 2006) and ultrastructural studies (Zauberman et al 2008;Xiao et al 2009), and several individual gene products have been characterized (for review, see Claverie and Abergel 2009); however, a systemic description of the molecular processes at work during the intracellular Mimivirus replication cycle (in particular the eclipse phase) is missing. During this phase, the Acanthamoeba cells are instructed by the infecting Mimivirus to build up a giant organelle-like ''virion factory'' that appears to centralize most of the metabolic processes leading to the synthesis of new Mimivirus particles (Suzan-Monti et al 2007;Claverie and Abergel 2009;Claverie et al 2009b).…”
mentioning
confidence: 99%
“…After the discovery of a unique vertex for herpes simplex virus (HSV) (15) and mimivirus (12,16), to the best of our knowledge, PBCV-1 is the third icosahedral, eukaryotic virus that has been recognized to have a unique vertex. It would therefore be possible that many more icosahedral eukaryotic viruses may require unique vertices for the successful execution of their life cycle.…”
mentioning
confidence: 99%
“…Some icosahedral viruses, including tailed bacteriophages, HSV (15,23), mimivirus (12,16), and PRD1 (21,24), have a specialized pentameric vertex that is associated with genomic packaging and/or cell entry. Even the small icosahedral poliovirus has or develops a special pentameric vertex when delivering its genome to its host (25).…”
mentioning
confidence: 99%